An Arab development bank : institutionalising change in Middle East - James M. Dorsey (2012)
Autocratic regimes and pro-democracy protesters in the Middle East and North Africa agree on the need for sustainable economic growth and integration into a globalised world. To achieve that, the region needs an Arab Development Bank like the development engines in Asia, Africa and Latin America.